2016
DOI: 10.1002/eat.22512
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of health related quality of life in anorexia nervosa

Abstract: Findings of the present study suggest that BMI and comorbidity might be more relevant to HRQoL impairments in AN than age, diagnostic subtype, duration of the ED or current psychopathology. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:630-634).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…An extremely low body weight due to malnutrition and starvation propels a cascade of medical sequelae which can have detrimental and lasting effects on health and functioning (Mehler & Brown, 2015). Research utilizing generic measures or health-related quality of life have shown a larger role for BMI in predicting impairment as related to physiological aspects of illness (e.g., pain, mobility) (Weigel et al, 2016), than studies such as ours which investigated self-reported impairment perceived as secondary to ED. The current investigation lends greater insight into the intense drive for thinness observed clinically in AN, as well as the persistent lack of recognition of the seriousness of low BMI despite the associated medical implications.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…An extremely low body weight due to malnutrition and starvation propels a cascade of medical sequelae which can have detrimental and lasting effects on health and functioning (Mehler & Brown, 2015). Research utilizing generic measures or health-related quality of life have shown a larger role for BMI in predicting impairment as related to physiological aspects of illness (e.g., pain, mobility) (Weigel et al, 2016), than studies such as ours which investigated self-reported impairment perceived as secondary to ED. The current investigation lends greater insight into the intense drive for thinness observed clinically in AN, as well as the persistent lack of recognition of the seriousness of low BMI despite the associated medical implications.…”
Section: Discussionmentioning
confidence: 57%
“…As a secondary aim, we investigated the unique associations between ED-related impairment and core cognitive and behavioral features of ED, including severity of BMI. This is an understudied issue, as prior investigations of the unique contributions of individual eating disorder features to EDrelated impairment have either utilized community samples (Hovrud & De Young, 2015;Jenkins, Rienecke, Conley, Meyer, & Blissett, 2015) or mixed diagnostic samples (Dahlgren et al, 2017), or have more broadly investigated correlates of health-related QOL rather than illness-specific impairment (Abbate-Daga et al, 2014;Weigel, Konig, Gumz, Lowe, & Brettschneider, 2016).…”
mentioning
confidence: 99%
“…Moreover, adult as well as adolescent patients with AN report a reduced health‐related quality of life (HRQoL), especially in mental health domains (Jenkins et al, ). Lower BMI, higher levels of depression, and higher levels of somatic complaints and organic comorbidities seem to be related to a lower HRQoL (Martín, Padierna, Loroño, Muñoz, & Quintana, ; Weigel, König, Gumz, Löwe, & Brettschneider, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research outside the eating disorder field underlines the negative consequences of a high somatic symptom severity on health care use (Gierk et al, ), impairments in quality of life (Kocalevent, Hinz, & Brähler, ; Kohlmann, Gierk, Hummelgen, Blankenberg, & Löwe, ), functional impairments like days of sick leave (Hoedeman, Blankenstein, Krol, Koopmans, & Groothoff, ), and the outcome of psychological treatments (Uher et al, ). In the field of anorexia nervosa, somatic symptom severity significantly predicted impairments in quality of life (Weigel, König, Gumz, Löwe, & Brettschneider, ). Further research to clarify the consequences of somatic symptom severity on psychological and functional impairments in both anorexia and bulimia nervosa is crucial to decrease subjective burden of eating disorders and to improve the clinical management of eating disorders (e.g., McClelland et al, ).…”
Section: Introductionmentioning
confidence: 99%